“It Has Been so Long Since I Last Wrote to You, yet I Have Been Writing This Letter for Such a Long Time…”: The Letters of Janina Degutytė to Teresė Ramanauskaitė Bukauskienė - Raškevičiūtė, Jurgita Žana Žana (Literatūra, 2018)
[full article in Lithuanian; abstract in English] All of the known letters of the poet Janina Degutytė (1928–1990), addressed to Teresė Ramanauskaitė-Bukauskienė (1928–1990), are published in this work. The thirty letters were written during the period of 1954–1968. These letters belong to the early epistolary period of the poet and, in a metonymical sense, reflect her correspondence of that time that took place between the Lithuanian philologists who had become close during their studies in Vilnius University. These are long letters, written as narratives, revealing the desire to speak up, to give an account of one’s life, environment, activities and hardships. They reveal a strong desire to communicate and an underlying feeling of the lack of communication, essentially affecting the form and contents of the letter; thus, the letter becomes an attempt to compensate for the lack of a communicative society, a society which has suddenly been lost, since the new provincial environment is perceived as alien and non-communicative. This correspondence exhibits the most important recurring features of the epistolary heritage of the poet of this period: what it was like to live up to the obligation of teaching in the province, which has been very little documented and described to date; what were the living conditions of a young teacher and how much effort they demanded to endure; how Degutytė experienced the tension between teaching, her vocation as a poet and the poor living conditions; how her health deteriorated because of this tension; what radical states the poet underwent by dividing her energy between her students and her poetry. These letters also tell an almost Cinderella-like story of Degutytė’s career – a very ambitious+ and emotional, but diffident and poor, teacher is transformed into a poet living in a sunlit apartment. These letters uncover all the major steps made in attaining a strong sociocultural status.